Vaccination take-up and health: Evidence from a flu vaccination program for the elderly - Ylenia Brilli; Claudio Lucifora; Antonio Russo; Marco Tonello (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2019)
We analyze the effects of a vaccination program providing free flu vaccine to individuals aged 65 or more on take-up and hospitalization. By using linked patient-general practitioner (GP) data, we implement a regression discontinuity design around the threshold at age 65. We find that the program increases vaccination take-up by 6 percentage points, which corresponds to 75% of the take-up for non-eligible individuals, and reduces the probability of hospitalization by about 44%. We show that the effect on take-up is not entirely due to an income channel, and that the effect on health is mainly driven by patients with higher-quality GPs and emergency hospitalizations.
Keywords: I12; I18; J10; 330; vaccination; influenza; public health; health prevention policies